Pengaruh Adana Gaya dalam Kepemimpinan Kepada Sekolah Terhadap Kinerja Guru - Bintha Ustafiano; Kasman Rukun; Muhammad Giatman (Universitas Muhammadiyah Surakarta, 2021)
Leadership style is a way that a leader in running the organization he leads. Leadership style has an effect on the performance of his subordinates. There are many types of leadership styles that leaders can use such as authoritarian, democratic, and laissez- faire leadership styles. The principal as a school leader should be able to choose a suitable leadership style used to perform school functions well by taking into account the aspects that influence the leadership style. One of the performance that principals need to pay attention is the performance of teachers. Teachers are a very dominant factor in education in general, because teachers hold responsibility in the learning process, where the learning process is at the core of the overall educational process. It is therefore important for principals to choose a suitable leadership style to improve teachers' performance in educating learners